Creation and management of Environmental Protection Areas: among actors, interests, uses, conflicts and the dilemma of conservation at Brazilian biomes Atlantic Forest and Cerrado (Terr@ Plural, 2020)
This paper aims to analyze the environmental management and conservation dilemma in the SNUC categories, especially the Environmental Protection Area (APA), with emphasis on the Atlantic Forest and the Cerrado. Much of the area designated for Conservation Units (UCs) in the country has been decreed as APA, a category widely criticized by the literature for involving highly urbanized areas whose use for tourism, farming, and mining hinder the management and conservation. It is essential, in this context, to establish partnerships with owners, reevaluate the proliferation of APAs, promote forest connectivity and prioritize critical Environmental Education in participatory management to resolve conflicts and stimulate conservation of natural resources.
Keywords: Socio-environmental conflicts; Biodiversity; Environmental education; Participative management